Impact of COVID-19 on service delivery in radiology and radiotherapy. (October 2022) - Mc Fadden, S.; Flood, T.; Shepherd, P.; Gilleece, T.
Abstract: Introduction: The COVID-19 pandemic has had a profound impact on radiography services globally. The reshaping of service delivery continues to impact patient management and the experience of the radiography workforce should be evaluated to determine how effective service delivery can be maintained in the ongoing and post-pandemic world. Methods: A mixed methods approach was adopted. Questionnaires, designed using Qualtrics (Qualtrics, Provo, UT) online survey software, were used to survey radiographers throughout Northern Ireland (NI). Semi-structured interviews were conducted with radiography service managers in the NHS and private sector in NI. All interviews were digitally recorded, transcribed and coded independently by 2 researchers. Results: A total of 106 Radiographers completed the online survey i.e. 82 Diagnostic and 24 Therapeutic. Variations were reported regarding staff concern for contracting COVID-19 and passing it on. Clinical workload was reported to fluctuate during the early period of the pandemic, however, both diagnostic and therapeutic radiographers reported workloads which were higher than normal at the time of the data collection. Nine service managers participated in the interviews plus two band 8 superintendent radiographers. Staff faced many challenges whilst delivering services due to COVID-19. The two most frequently cited challenges included issues related to (i) Implementation of PPE and (ii) Changes to work practices. Conclusion: A pre-prepared pandemic plan should be established and stress tested for the future. The plan should be devised in consultation with both the public and private sector to determine the very best use of resources. Implications for practice: The radiography workforce has worked continuously throughout the pandemic and needs to be supported to deal with the potential increase in demand for services in the post-pandemic world.